2017
DOI: 10.20517/2394-4722.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Combination of insulin-like growth factor-1, IGF binding protein-3, chromogranin A and prostate specific antigen can improve the detection of prostate cancer

Abstract: Aim: Prostate cancer (PCa) is the second most prevalent male cancer worldwide and designated the sixth most frequent male cancer in Arab countries. Although prostate specific antigen (PSA) has become the best and most valuable biomarker for screening of PCa, elevated levels of PSA can reflect the presence of malignant cells but can overlap with benign prostatic diseases. There is a necessity to develop and improve current tools for early detection and diagnosis of PCa. This study was done to evaluate the valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A high IGF-I to IGFBP-3 ratio was linked with an increased risk of prostate cancer and could be used as a predictor for prostate cancer development (168). On the other hand, another study by Saleh SAK et al reported that changes in the serum levels of IGF-I and IGFBP-3 were not considered pre-diagnostic risk factors for prostate cancer development (142). Besides, serum levels of total PSA and free/total PSA ratio were found to be higher in prostate cancer patients (142).…”
Section: The Impact and Expression Of The Igf Family In Neoplastic Pr...mentioning
confidence: 99%
See 3 more Smart Citations
“…A high IGF-I to IGFBP-3 ratio was linked with an increased risk of prostate cancer and could be used as a predictor for prostate cancer development (168). On the other hand, another study by Saleh SAK et al reported that changes in the serum levels of IGF-I and IGFBP-3 were not considered pre-diagnostic risk factors for prostate cancer development (142). Besides, serum levels of total PSA and free/total PSA ratio were found to be higher in prostate cancer patients (142).…”
Section: The Impact and Expression Of The Igf Family In Neoplastic Pr...mentioning
confidence: 99%
“…IGFBP-3 is the most prevalent form of the IGFBPs, which has been linked with prostatic growth. The majority of serum and prostatic IGF-I binds to IGFBP-3, thus regulating its concentrations ( 142 ). IGFBP-3 was identified to have anti-tumor effects by regulating multiple processes such as adhesion, motility, proliferation, and invasion of prostate cancer cells ( 143 ).…”
Section: The Impact and Expression Of The Igf Family In Neoplastic Pr...mentioning
confidence: 99%
See 2 more Smart Citations